2022
DOI: 10.1126/sciadv.abj2797
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of proBDNF/p75 NTR signaling in antibody-secreting cells drives systemic lupus erythematosus

Abstract: Inappropriate expansion of antibody-secreting cells (ASCs) is typical of systemic lupus erythematosus (SLE), but the regulatory signaling of pathogenic ASCs is unclear. The present study shows that brain-derived neurotrophic factor precursor (proBDNF) and its high-affinity pan-75 neurotrophin receptor (p75 NTR ) are highly expressed in CD19 + CD27 hi CD38 hi ASCs in patients with SLE and in CD19 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Blockade of proBDNF by monoclonal antibody suppressed the activity of ASCs and ameliorated pristane-induced lupus progression. 13 Thus, these data strongly imply an important role of B cell-derived proBDNF in the pathology of SLE disease.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Blockade of proBDNF by monoclonal antibody suppressed the activity of ASCs and ameliorated pristane-induced lupus progression. 13 Thus, these data strongly imply an important role of B cell-derived proBDNF in the pathology of SLE disease.…”
Section: Discussionmentioning
confidence: 75%
“… 12 Recently, we have reported a pathological role of proBDNF in SLE by promoting the differentiation of antibody-secreting cells (ASCs) and the production of autoantibodies, indicating its potential as a therapeutic candidate for SLE treatment. 13 However, whether proBDNF specifically affects CD3 + B220 + cells in MRL/lpr mice is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many studies show that proBDNF is increased in major depression and elicits opposing effects to that of BDNF via binding p75NTR and co-receptor sortilin to mediate neuronal apoptosis, neurite collapse, inhibition of neurogenesis and activated inflammatory response (Sunet al , 2012;Li et al , 2017;Ho et al , 2019;Hu et al , 2021). Many clinical and animal studies have highlighted associations between proBDNF signaling or high levels of inflammatory markers and autoimmune states, such as multiple sclerosis (MS), rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) (Hu et al , 2021;Shen et al , 2022;Yang et al , 2022). Perhaps surprisingly, depression and anxiety disorder are exceedingly common in RA but the underlying overlapping pathogenesis are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the upregulation of proBDNF and its receptor p75NTR in macrophages, monocytes, lymphocytes and microglia in a variety of neurological conditions, including spinal cord injury, multiple sclerosis, lipopolysaccharide(LPS)-induced sepsis, lupus erythematous (Luo et al , 2020;Shen et al , 2022) and Toxoplasma infection (Dusedau et al , 2019;Hu et al , 2021;Klawonn et al , 2021). Only a few studies found that BDNF and proBDNF can be released from B cells and T cells, contributing to B cell development or survival, and T cell maturation (Schuhmann et al , 2005;Linker et al , 2015).…”
Section: Expression Pattern Of Probdnf/p75ntr In Peripheral Immune Cellsmentioning
confidence: 99%
“…Brain-derived neurotrophic factor precursor (proBDNF) is an intermediate during the synthesis of mature BDNF. 6 As a functional protein, proBDNF binds to the high-affinity pan-p75 neurotrophin receptor (p75 NTR ), which is also a low affinity nerve growth factor (NGF) receptor and BDNF. 7,8 The activated p75 NTR further elicits the downstream signals, such as nuclear factor kappa B (NF-κB), to induce inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%